2020
DOI: 10.1021/acs.jpclett.0c02331
|View full text |Cite
|
Sign up to set email alerts
|

Negative Capacitance and Inverted Hysteresis: Matching Features in Perovskite Solar Cells

Abstract: Negative capacitance at the low-frequency domain and inverted hysteresis are familiar features in perovskite solar cells, where the origin is still under discussion. Here we use Impedance Spectroscopy to analyse these responses in methylammonium lead bromide cells treated with lithium cation at the electron selective layer/perovskite interface and in iodide devices exposed to different relative humidity conditions. Employing the Surface Polarization Model, we obtain a time constant associated to the kinetics o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
117
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 83 publications
(124 citation statements)
references
References 40 publications
(111 reference statements)
7
117
0
Order By: Relevance
“…Recent studies by Alvarez et al, have shown that the faster time response or kinetics lead to a behavior dominated by ionic diffusion. [36] In the present case, faster ionic diffusion is expected in IPA-PSCs because of larger grains' sizes. This result signifies that the sizes of the grains affect the impedance response of PSCs.…”
Section: Effect Of Grain Size and Boundaries In Perovskite Layer On The Low-frequency Arc In Eis Of Pscmentioning
confidence: 56%
See 2 more Smart Citations
“…Recent studies by Alvarez et al, have shown that the faster time response or kinetics lead to a behavior dominated by ionic diffusion. [36] In the present case, faster ionic diffusion is expected in IPA-PSCs because of larger grains' sizes. This result signifies that the sizes of the grains affect the impedance response of PSCs.…”
Section: Effect Of Grain Size and Boundaries In Perovskite Layer On The Low-frequency Arc In Eis Of Pscmentioning
confidence: 56%
“…The reduction in the capacitance values was previously observed after Li þ treatment of the TiO 2 layer. [36] The authors found that the presence of Li þ at ETL/perovskite interface could reduce the accumulation of the intrinsic ions, and especially avoid the interactions at ETL surface by reducing the density of holes. [36] In line with the results shown in Figure 2d, a higher value of R HF and R LF in TiO 2 /SnO 2 PSC is obtained as compared with that of the reference device, which suggests lower recombination and higher value of V OC (Figure 2f ).…”
Section: Effect Of Etl/perovskite Interface Engineering On the Low-frequency Arc In Eis Of Pscmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, due to the nature of these devices, electrochemical redox processes are considered to be commonplace 9 , 10 . Other types of electrochemical processes, such as adsorption–desorption and diffusion, seen more commonly in similar solid state devices, such as, perovskite solar cells 11 , 12 , lithium-ion batteries 13 , fuel cells 14 , OLEDs 15 , Fe doped SrTiO3 (STO) thin films 16 , may also materialize inside memristors, due to the abundance of oxygen vacancies and other interstitials, thought to be the cause of the resistive switching phenomenon 17 . Many of these processes are better identified in an Alternating Current (AC) environment.…”
Section: Introductionmentioning
confidence: 99%
“…According to the literature, the normal hysteresis presented in PSCs is attributed to the existence of a capacitive current before reaching the steady-state current, namely, there is an accumulation of charges in the forward scan ("capacitor filling") and a release of charges in the reverse scan ("capacitor emptying") [40]. On the other hand, the inverted hysteresis is intimately related to phenomena of negative capacitance, which are associated with surface interactions with vacancies/ions at the electron transport layer/perovskite interface [41]. A more and in-depth discussion on the origins of the obtained PV parameters variation is given in the following paragraphs through the quantum efficiency and impedance measurements on PSCs.…”
mentioning
confidence: 99%